QUALITY CONTROL ANALYSIS WITH SQC (STATISTICAL QUALITY CONTROL) METHOD ON RAFT FOUNDATION WORK - Bagus Soebandono (Jurnal Scientia, 2023)
It is necessary to control the quality of the concrete, so that the concrete specification requirements plan is achieved. The results of quality control research on PT "X"s ready mix concrete products based on SNI 2874-2019 requirements in regarding structural concrete requirements for buildings and explanations, it's found that the concrete produced by PT”X” for the raft foundation casting work on project "Z" can be accepted and qualifies as concrete with a quality of 30 Mpa. Meanwhile, the uniformity analysis using the X and R control charts in the SQC method obtained an uncontrolled process with a process capability value of Cp = 0.601; Cpk = 0.577 <1 this indicates a low process capability, needs to be improved, this process produces many products that do not align to the center line and causing a deviation patterns on the X and R control charts. The deviation pattern indicates that the ready mix product of PT "X"s that used in Project "Z" raft foundation is not uniform, however, the overall concrete quality achieved the technical specification requirements.